Kebijakan Kriminalisasi Pada Tindak Pidana Perzinahan Dalam Rancangan Undang-Undang Hukum Pidana Berdasarkan Pembaharuan Hukum Pidana - Muhamad Samsudin; Margo Hadi Pura (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2023)
Products of criminalization in Indonesia can be seen in article 284 of the Criminal Code, the adultery provisions in the Criminal Code that are currently in effect aim to criminalize perpetrators of extramarital affairs where one or both of the perpetrators of intercourse are people who are already bound by previous marriage ties. In addition, Article 284 of the Criminal Code is an absolute criminal offense which does not allow the act to be punished. If no one complains from the aggrieved party (the husband or wife who betrayed their partner) and as long as the case has not been examined before the court, the complaint can always be withdrawn. It can be concluded that the designer of the article criminalized this crime of adultery on the grounds of maintaining the sanctity of the marriage bond for people who are married. The method used in this research is normative legal research method. In this method, law is conceptualized as what is written in a statutory regulation (law in books) or law is conceptualized as a rule or norm that is used as a benchmark for human behavior so that it is considered appropriate. Normative legal research is carried out on secondary data such as scientific journals, books, previous research, and laws and regulations related to the object of research. Regulations on the crime of adultery in the future should pay attention to harmony with central socio-political, socio-philosophical, and socio-cultural values that can facilitate an act committed by an unmarried person or both of whom are not bound by a marriage. In formulating these regulations, one must look at the objectives of the law itself, namely certainty, justice and expediency.